The Humanities among the Strings of Neoliberlism - Rodríguez Reyes, Abdiel (2014)
This article problematizes the situation of the humanities in the rise of neoliberalism. It proposes that to understand the modern world, it is necessary to problematize and interrelate humanistic fields of knowledge, science and technology. It is also critical to consider the vision we have of education at the exclusive service of the market society and the financial elites